STRATEGI CONTENT MARKETING DALAM MEMASARKAN PRODUK LOKAL Y.O.U SKINCARE (STUDI KASUS AKUN @YOUBEAUTY_IDN) - Tuty Mutiah, Mutiah; Himalaya, Anita; Anisti , Anisti (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
The utilization of Instagram social media as a platform for content marketing strategy, particularly through the implementation of the Smart Digital Content Marketing (SDCM) model, is the primary focus of this study. It centers on the analysis of strategies employed by the @Youbeauty_idn account in promoting Y.O.U Beauty products. This research demonstrates the successful implementation of various strategies aligned with the SDCM model. Effective strategies include social media optimization through building a substantial follower base and maintaining posting consistency, collaboration with influencers to enhance product visibility, presenting compelling offers that capture the attention of Instagram users, and gathering user feedback to improve product quality and marketing strategies. Furthermore, the importance of fostering strong relationships with followers to maintain consumer loyalty is highlighted in this study. By applying these strategies, @Youbeauty_idn has effectively enhanced awareness, trust, and sales of Y.O.U Beauty products via the Instagram platform. This research provides valuable insights into how social media, particularly Instagram, can effectively serve as a content marketing tool for promoting local products such as Y.O.U Skincare.